KONFIRMASI AVIAN PARAMYXOVIRUS TIPE 1 (APMV-1) SECARA HISTOPATOLOGIS, SEROLOGIS, DAN MOLEKULER (Confirmation of Avian Paramyxovirus Tipe 1 (APMV-1) Infection by Histopathology, Serology, and Molecular Method) - I Gusti Agung Arta Putra; Anak Agung Ayu Mirah Adi (Jurnal Kedokteran Hewan, 2016)
Research was conducted to detect APMV-1 infection by examining microscopic lesions of chicken suspected ND and confirming the causative agent with serological and molecular assay. Samples obtained from commercial and back yard farm in 9 regencies and city of Bali Province were tested by rapid test for AIV antigen detection. AI negative samples were necropsied, then brain, lungs, and intestines were collected for histopathological examination. Samples tissue of brain, lung, spleen, and intestine were taken aseptically for viral isolation and amplification. Infected allantoic fluid was collected and tested by hemagglutination assay (HA) and hemagglutination inhibition (HI) test to prove APMV-1 serologically. Viral ribonucleic acid was isolated and subsequently reverse transcribed by reverse trasncription reaction followed by amplification by polymerase chain reaction to multiply the cDNA. Microscopically, perivascular cuffing (20%), endoteliosis (75%), and gliosis (75%) were found in the brain. In the lung, an interstitialis pneumonia (50%), lobar pneumonia (5%), and proliferation of pneumosit type 2 (100%) were observed. The most prominent intestinal lesions were catarrhal enteritis (75%) and hemorrhagic necrotizing enteritis (10%). Confirmation of the 20 isolates obtained in this study both serologically and molecularly were positive APMV-1. Moreover PCR results showed that 80% of its amplicon showed a single band and 20% still require some optimizations to get single good bands.